ROLAND BARTHES' SEMIOTIC ANALYSIS OF THE MEANING OF THE FATHER-CHILD RELATIONSHIP IN THE VIDEO CLIP "TERBURANGAN DI WAKTU" BY BARASUARA (2023) - Suci Shinta Lestari; M Rahman; Fenny Anita (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Music videos are a form of audio-visual media that functions not only as a promotional medium for songs but also as a means of conveying social and cultural meanings through visual symbols. One music video that presents an emotional representation of family relationships is “Terbuang in Time” by Baradasar, released in 2023. This music video depicts the changing dynamics of the father-6 child relationship over time, in which the father's role shifts from a caregiver and protector to an individual who is cared for by his child. The research problem addressed in this study concerns how the meaning of the father–child relationship is represented in the music video “Terbuang in Time” by Baradasar (2023). This study employs a qualitative approach using Roland Barthes' semiotic analysis method, which focuses on interpreting signs through three levels of signification: denotation, connotation, and myth. The object of the study is focused on visual scenes representing interactions between father and child within the music video. Data were collected through visual observation, documentation, and literature review related to semiotics, visual communication, and family communication studies. The data analysis process was conducted by identifying visual signs and interpreting their meanings based on Barthes' theoretical framework. The findings indicate that the music video represents the father–child relationship as an emotional bond grounded in affection, care, and intergenerational responsibility. At the levels of connotation and myth, the video constructs meanings related to a child's moral responsibility toward parents, the importance of reciprocity, and shifting societal perceptions of fatherhood. The father is no longer described solely as an authoritative figure but also as an individual characterized by vulnerability and emotional sensitivity. This study is expected to contribute to the development of semiotic studies in audio-visual media, particularly those examining representations of family relationships.